Hubungan Pengetahuan Ibu dan Dukungan Suami dengan Keberhasilan Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Gilingan Kota Surakarta - Sahira, Batrisya; Kisnawaty, Sudrajah Warajati; Firmansyah, Firmansyah (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Mother's milk (ASI) is the best food for babies, especially in the first months of life. Coverage of exclusive breastfeeding in Surakarta City in 2023 has reached the target (81.84%), however exclusive breastfeeding in the Gilingan Community Health Center Work Area, Surakarta City has still not reached the target, namely 64.4% (Surakarta City Health Profile, 2023). This study aims to determine the relationship between maternal knowledge and husband's support with the success of providing exclusive breastfeeding in the Gilingan Community Health Center Working Area, Surakarta City. This type of research is analytical quantitative research, using a survey design cross sectional. The sample consisted of 69 baduta mothers, taken using this technique stratified random sampling. Data on mother's knowledge and father's support were collected using a questionnaire. Statistical test of data using test Chi-Square. Based on the research results obtained p-value 0.000 (<0.05) means there is a relationship between maternal knowledge and husband's support with the success of exclusive breastfeeding